Faktor Risiko Kejadian Recurrent Respiratory Infection pada Anak Usia 2-5 Tahun - NOPRIYAN PUJOKUSUMA; ETI PONCORINI PAMUNGKASARI; SETYO S RAHARDJO (Faculty of Medicine Universitas Sebelas Maret, 2018)
Introduction: Acute Respiratory Infection (ARI) is the most prevalent disease with high mortality and morbidity on infant. ARI that happens more than five times annually is called Recurrent Respiratory Infection (RRI). Some mortality of ARI comes from kind of ARI that developed from diseases that could be prevented by immunization. This study aimed to find correlation between immunization status, nutritional status, crowding, smoker in house, mother education level, family income level and RRI incident on children age 2-5 years old in Sibela Primary Health Care (PHC) work area, Surakarta.Methods: This was an observational analytic study with cross-sectional approach. Sample for this study was children age 2-5 years old from Sibela PHC work area, Surakarta. Sample was taken by cluster sampling method as much as 121 children, the parent interviewed using questioner and children was measured for their height and weight. Data of immunization history was obtained from Kesehatan Ibu dan Anak (KIA) Book and PHC data information system for ARI diagnosis. Data was analyzed using chi-square and logistic regression.Result: Chi-square result shows significant correlation between incomplete immunization status and incident of RRI (p=0,000) and OR = 18,774. Logistic regression results shows significant correlation between immunization status and incident of RRI (p=0,000; OR=21,3). Conclusions: Incomplete immunization status significantly correlate to increasing RRI incident 21,3 times on children age 2-5 years old than children which acquired complete immunization status. Nutritional status, crowding, smoker in house, mother educational level, and family income level has no significant correlation with RRI incidence.